POTENTIAL OCCUPATION IN HALAL INDUSTRY FOR REINFORCEMENT SHARIA ECONOMIC LAW - Nurdeng Deuraseh; Bagas Heradhyaksa (Fakultas Hukum, Universitas Diponegoro, 2020)
One of the main critical but interesting issues today to be discussing and debated even there is no right or wrong answer to this issue, is the job opportunity and career for young graduates in almost all educational disciplines especially social and religious science which including also halal science in the current of uncertain and bad economy situation. It is a known fact that everyone of us including myself has gone through a rough start in our life or career upon graduations many years ago. We grabbed whatever came along the way before we built our successful career. We have to pick up any jobs along the line as we have got bills to pay and stomach to feed and later on family to take care. In this article, discussion will be made to identify the challenge and job opportunity for halal science graduates. Its challenge is not so critical as others because halal education is a new discipline that rooted in the Holy Quran and the Sunnah of the Prophet Muhammad (s.a.w) and emerges in modern life as a result of high demand of global society since halal business proposition is ready to be the next world market force in global. In this regards, various Islamic political policies have been determined and implemented in Muslim countries notably Negara Brunei Darussalam for the purpose of disseminating and developing halal education for global reach. It is found that the graduates of halal science may try to secure their job and career in many positions notably as government servant in several Ministries i.e.., education, health, agriculture, trade, finance, etc.; halal auditors; halal consultants; working in Industry/company; research assistant & researcher in Universities; Educationist i.e., teacher; religious preachers (Da`i); academician; halal- entrepreneur and MA & PhD Students.